A selective window after the food-intake period favors tolerance induction in mesenteric lymph nodes - Barrios, Bibiana Elisabet (2019)
Biological rhythms are periodic oscillations that occur in the physiology of the organism and the cells. The rhythms of the immune system are strictly regulated and the circadian alteration seems to have serious consequences. Even so, it is not clear how the immune cells of the intestinal mucosa synchronize with the external environment. Besides, little is known about the way in which biological rhythms affect the critical functions of intestinal immunity, such as oral tolerance. We studied fluctuations in the relevant parameters of intestinal immunity at four different times throughout the day. By using multivariate statistical tools, we found that these oscillations represent at least three different time frames with different conditions for tolerance induction that are altered in Per2ko mice lacking one of the clock genes. Our results allowed us to characterize a window in the final stage of the dark phase that promotes the induction of specific regulatory populations and favors its location in the lamina propria. We show here that, at the end of the intake, the entry of luminal antigens, soluble factors, and leukocyte populations converge in the mesenteric lymph nodes (MLN) and display the greatest potential of the tolerogenic machinery.